A non-parametric test of variability of Type Ia supernovae luminosity and CDDR. Issue 1 (1st January 2022) - Kumar, Darshan; Rana, Akshay; Jain, Deepak; Mahajan, Shobhit; Mukherjee, Amitabha; Holanda, R.F.L.
Abstract: The first observational evidence for cosmic acceleration appeared from Type Ia supernovae (SNe Type Ia) Hubble diagram from two different groups. However, the empirical treatment of SNe Type Ia and their ability to show cosmic acceleration have been the subject of some debate in the literature. In this work we probe the assumption of redshift-independent absolute magnitude (MB ) of SNe along with its correlation with spatial curvature (Ωk0 ) and cosmic distance duality relation (CDDR) parameter (η(z)). This work is divided into two parts. Firstly, we check the validity of CDDR which relates the luminosity distance (dL ) and angular diameter distance (dA ) via redshift. We use the Pantheon SNe Ia dataset combined with the H(z) measurements derived from the cosmic chronometers. Further, four different redshift-dependent parametrizations of the distance duality parameter (η(z)) are used. The CDDR is fairly consistent for almost every parametrization within a 2σ confidence level in both flat and a non-flat universe. In the second part, we assume the validity of CDDR and emphasize on the variability of M_B and its correlation with Ωk0 . We choose four different redshift-dependent parametrizations of MB . The results indicate no evolution of MB within 2σ confidence level. For all parametrizations, the best fit value of Ωk0 indicates a flat universe at 2σ confidence level. However a mild inclination towards a non flat universe is also observed. We have also examined the dependence of the results on the choice of different priors for H0 .